Detection of CTV by immunoprinting in the Eastern Mediterranean region of Turkey - Yilmaz M.; Baloglu S. (Proceedings of the Mediterranean network on certification of citrus. 1995-1997, 1998)
Direct immunoprinting was used to detect CTV in samples taken from different Turkish provinces, including those which had already been found positive by ELISA. This technique is as reliable as ELISA if fresh tissues are used in the printing. It may prove very useful during certification mainly in the nursery.
Round Table on: Citrus Virus and Virus-like Diseases and Certification: State of the Art, 1995/07/21, Bari (Italy)